2016
DOI: 10.1007/s00240-016-0956-8
|View full text |Cite
|
Sign up to set email alerts
|

Kidney stones diseases and glycaemic statuses: focus on the latest clinical evidences

Abstract: Diabetes and obesity are already recognized as potential risk factors for nephrolithiasis, especially for uric acid stones. Insulin resistance and hyperinsulinemia actively contribute to impaired ability to excrete an acid load and altered ammonium production, leading to a lower urinary pH compared to non-diabetic controls. All these electrolytic disorders play an important role in stone formation and aggregation, especially in uric acid stones. There are still missing points in scientific evidence if the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
0
12
0
7
Order By: Relevance
“…Given the risk of KS recurrence, high morbidity, the necessity of endo-urological or surgical interventions, early diagnosis and specialized management of KSD is indicated [74]. Awareness is essential to rapidly identify the pro-lithogenic metabolic abnormalities, assess the coexistence of renal and/or cardiovascular complications with the aim of controlling KSD and slowing down the CKD progression with adequate treatment [75,76].…”
Section: Kidney Stones As a Multi-systemic Illnessmentioning
confidence: 99%
“…Given the risk of KS recurrence, high morbidity, the necessity of endo-urological or surgical interventions, early diagnosis and specialized management of KSD is indicated [74]. Awareness is essential to rapidly identify the pro-lithogenic metabolic abnormalities, assess the coexistence of renal and/or cardiovascular complications with the aim of controlling KSD and slowing down the CKD progression with adequate treatment [75,76].…”
Section: Kidney Stones As a Multi-systemic Illnessmentioning
confidence: 99%
“…Epidemiologic studies have suggested the positive association between diabetes and nephrolithiasis, but whether there is also a link between prediabetes and risk for nephrolithiasis is not yet well established, with conflicting results available from previous research. 7,11,[13][14][15][16][17] In most of these studies, the primary exposure was metabolic syndrome; thus, glucose level was examined as 1 metabolic syndrome component using a dichotomous category (prediabetes combined with diabetes or not) without consideration of differential effects of prediabetic and diabetic levels on nephrolithiasis risk.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although multiple epidemiologic studies have supported the effect of diabetes on nephrolithiasis, the association between prediabetes and nephrolithiasis remains unclear and studies of this issue are limited. 7 Insulin resistance, a key feature of prediabetes and type 2 diabetes, affects ammoniagenesis in the renal tubule, leading to urine acidification and subsequent formation of urinary stones. 8,9 Also, hyperglycemia-related glycosuria, which is related to increased urinary calcium, phosphorus, and uric acid excretion, could induce urinary stone formation.…”
mentioning
confidence: 99%
“…Upon obstruction, a series of complications occur, such as local damage, infection, bleeding, and hydronephrosis [ 38 ]. In particular, insulin resistance leads to impaired UA excretion at a low urinary pH, contributing to the formation of urate stones [ 39 ].…”
Section: Mechanisms Of Hyperuricemia-induced Renal Injurymentioning
confidence: 99%